The effects of Contingent Convertible (CoCo) bonds on insurers' capital requirements under solvency II - Tobias Niedrig; Helmut Gründl (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The Liikanen Group proposes contingent convertible (CoCo) bonds as a potential mechanism to enhance financial stability in the banking industry. Especially life insurance companies could serve as CoCo bond holders as they are already the largest purchasers of bank bonds in Europe. We develop a stylized model with a direct financial connection between banking and insurance and study the effects of various types of bonds such as non-convertible bonds, write-down bonds and CoCos on banks' and insurers' risk situations. In addition, we compare insurers' capital requirements under the proposed Solvency II standard model as well as under an internal model that ex-ante anticipates additional risks due to possible conversion of the CoCo bond into bank shares. In order to check the robustness of our findings, we consider different CoCo designs (write-down factor, trigger value, holding time of bank shares) and compare the resulting capital requirements with those for holding non-convertible bonds. We identify situations in which insurers benefit from buying CoCo bonds due to lower capital requirements and higher coupon rates. Furthermore, our results highlight how the Solvency II standard model can mislead insurers in their CoCo investment decision due to economically irrational incentives.
Keywords: G11; G21; G22; G28; G32; 330; Contingent Convertible Capital; CoCo Bond; Basel III; Solvency II; Life Insurance; Interconnectedness